End‐of‐Day Price Manipulation and M&As. (28th June 2019) - Cumming, Douglas; Ji, Shan; Johan, Sofia; Tarsalewska, Monika
Abstract: Based on mergers and acquisitions (M&As) from over 45 countries from 2003 to 2014, we show that the presence of end‐of‐day (EOD) target price manipulation prior to M&As increases the probability of an M&A deal withdrawal, and decreases the premium paid. More detailed exchange trading rules that govern manipulation across countries and over time lower the probability of withdrawal, mitigate the negative impact of EOD manipulation on withdrawal and raise premiums paid. Finally, while there are fewer cases of acquirer price manipulations prior to M&As, the data indicates positive acquirer price manipulation in share M&As and increases the probability of deal withdrawal.